Science in Flux: NASA's Nuclear Program at Plum Brook Station, 1955-2005. - NEUSHUL, PETER (Isis: A Journal of the History of Science in Society, 2008)
This article reviews the book "Science in Flux: NASA's Nuclear Program at Plum Brook Station, 1955-2005," by Mark D. Bowles.